Measuring acute poverty in the developing world : robustness and scope of the Multidimensional Poverty Index - Alkire, S; Santos, M (Oxford Poverty & Human Development Initiative (OPHI), 2013)
This paper presents the Multidimensional Poverty Index (MPI), a measure of acute poverty, understood as a person’s inability to meet simultaneously minimum international standards in indicators related to the Millennium Development Goals and to core functionings. It constitutes the first implementation of the direct method to measure poverty for over 100 developing countries. After presenting the MPI, we analyse its scope and robustness, with a focus on the data challenges and methodological issues involved in constructing and estimating it. A range of robustness tests indicate that the MPI offers a reliable framework that can complement global income poverty estimates.